Endovascular Treatment of Right Heart Masses Utilizing the AngioVac System: A 6-Year Single-Center Observational Study - Aashish Katapadi; Lauren Richards; William Fischer; Suhail Q. Allaqaband; Tanvir Bajwa; M. Fuad Jan (Journal of Interventional Cardiology)
Objective. To describe our institution’s experience with the AngioVac system. Background. Intracardiac and intravascular masses previously required surgical excision, but now, there are a number of minimally invasive options. With the advent of vacuum aspiration, more specifically the AngioVac System (AngioDynamics, NY, USA), there exists a system with both low mortality and minor complications. However, the number of retrospective studies remains limited. Outcome data for high-risk patients are also limited. Methods. Data were collected and analyzed in patients who underwent AngioVac therapy at our tertiary care center from January 2014 to December 2020. Results. Our results demonstrated a 93.3% intraoperative success rate and a 100% intraoperative survival rate. However, a number of complications, including but not limited to hematomas, anemia, and hypotension, occurred, as described below. Conclusions. Our experiences demonstrated good outcomes and continue to support the usefulness of the AngioVac System. The data also support the use of AngioVac as a treatment option for the debulking or removal of right heart masses in critically ill patients.